Practical Protocol for Comprehensively Evaluating Sulfur-Fumigation of Baizhi Based on Metabolomics, Pharmacology, and Cytotoxicity - Deng, Ai-Ping; Kang, Chuan-Zhi; Kang, Li-Ping; Lyu, Chao-Geng; Zhang, Wen-Jin; Wang, Sheng; Wang, Hong-Yang; Nan, Tie-Gui; Zhou, Li; Huang, Lu-Qi; Zhan, Zhi-Lai; Guo, Lan-Ping (Frontiers in Pharmacology, 2022)
Sulfur Angelicae Dahuricae Radix (Baizhi) is a common medicinal herb in Asian countries. A practical protocol combining metabolomics, pharmacology, and cytotoxicity was developed to comprehensively evaluate the influence of sulfur-fumigation on the quality of Baizhi. Eight new sulfur-containing furocoumarins were found in sulfured Baizhi. Furocoumarins can be transformed into sulfur-containing compounds in sulfuring process, among which 1 and 3 were purified with relatively high abundance and identified as 3,4-dihydrobyakangelicin-4-sulfonic acid and (4R,12S)-3,4-dihydrooxypeucedanin hydrate-4-sulfonic acid (OXH-S), respectively. OXH-S was found to be an addition product of sulfite and oxypeucedanin hydrate (OXH-N). Then, the cytotoxicity and anti-inflammatory activity of OXH-N, OXH-S, extraction of sulfured (extraction-S), and unsulfured Baizhi (extraction-N) were evaluated. OXH-N and extraction-N were less toxic than OXH-N and extraction-N, respectively. OXH-N and OXH-S, extraction-N, and extraction-S showed no significant differences in anti-inflammatory activity. Based on these results, sulfur fumigation can reduce toxicity and does not influence the anti-inflammatory activity of Baizhi, even after its chemical composition changes; thus, appropriate sulfur-fumigation can be applied to Baizhi. The proposed protocol based on marker screening, pharmacology, and safety evaluation can provide scientific basis for standardization and regulation of sulfured Baizhi and other medical materials.